Political choices during the European Parliament elections as a model for civic responsibility of young people in Poland – the context of formal education - Kanclerz, Bożena (Kultura-Społeczeństwo-Edukacja, 2020)
The main axis of the narration in this article is the analysis of the electoral activity of young Poles from the perspective of the formal program of Citizenship Education in the area of shaping the attitudes of young people as active voters. The first part of the article presents the context of Polish civil society and the electoral activity of young Poles. The Author connects the analyses of youth electoral patterns to with the assessment of effectiveness of formal education, including textbook messages, in shaping and developing civic engagement in youth. The article presents the analysis of textbooks for civic education, as well as indicates some non-textual contexts for implementing civic education in Poland. The analysis of citizenship education textbooks becomes an opportunity to approximate multi-faceted challenge of shaping civil attitudes among young people in Poland.